I don't know the correct answer how this reduction should've be done. Should I simply put λfx.fx in a place of m and λzy.zzy in a place of n?

(λmnfx.mf(nfx) λfx.fx λzy.zzy)

  • $\begingroup$ You're on the right track. Pay special attention to the names of the variables as there is another reduction which must be performed before you can apply terms. $\endgroup$ – c.w.chambers Jun 22 '14 at 13:57
  • $\begingroup$ (λfx.f(f(fx))) I've figured answer like that, is that correct? Please praise my effort with correct answer or solution because I'am dying out of this lambda :( $\endgroup$ – Sheil Jun 22 '14 at 15:50

You have placed parenthesis around the two final variables in the body. I don't see that right-associativity supported in the stated problem where the third abstraction is \zy.zzy not \zy.z(zy).

I believe the answer is \fx.f(ffx) which is equivalent to \fx.f((ff)x).

Also, this is a duplicate question but I'm not sure how to link to the other one.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.